(untitled) (Communications in Computational Physics, 2018)
We present a robust approach to perform 3D nonrigid image registration suitable for large deformation and topology change, and develop a software package named DTHB3D Reg (Dynamic Truncated Hierarchical B-spline based 3D Image Registration). The optimum spatial transformation, defined using truncated hierarchical B-splines, is obtained through the minimization of an energy functional. The optimization process minimizes sum of squared difference in the intensity values of the grayscale images. Control points are dynamically updated without constructing large matrices as in finite element method. To improve the computational efficiency, an adaptive strategy carries out refinement only in the regions with large deformation. The proposed method is demonstrated on 3D synthetic and medical images to show robustness on topology change as compared to other image registration methods.